Comparing the accuracy of the urinary tract infection symptom assessment and the acute cystitis symptom score questionnaires in diagnosis of acute uncomplicated cystitis in women - Yi-Ju Chou; Shang-Jen Chang; Stephen Shei-Dei Yang (Investigative and Clinical Urology)
Purpose: The purpose of this study is to compare the accuracy of two commonly used questionnaires in diagnosing acute cystitis, i.e., the urinary tract infection symptom assessment (UTISA) and the acute cystitis symptom score (ACSS) questionnaires. Materials and Methods: From April 2021 to December 2022, we enrolled female patients with suspected symptoms of acute cystitis as the patient group. As a control group, we included asymptomatic females who came to the hospital for health check-ups. We calculated the accuracy of the two questionnaires in diagnosing acute cystitis and compared the difference in the area under the curve (AUC) of the two through the DeLong test. Results: A total of 89 and 43 participants were recruited for the patient and control groups, respectively. Both questionnaires include six symptoms: frequency, urgency, dysuria, incomplete bladder emptying, lower abdominal pain, and hematuria to diagnose acute cystitis. However, UTISA includes lower back pain as the 7th symptom. The sensitivity, specificity, and AUC of UTISA and ACSS were 85.4% versus 75.3% (p=0.091), 93.0% versus 93.0% (p>0.999), and 0.96 (95% CI 0.92–0.99) versus 0.90 (95% CI 0.83–0.94) (p<0.001), respectively. Conclusions: UTISA questionnaire demonstrates higher diagnostic accuracy compared to ACSS questionnaire. ACSS has lower sensitivity probably due to its limited assessment of low back pain and the objective definition of the severity of frequency that prevents patients from responding based on subjective severity.